Modifikasi Sistem Kontrol Suhu pada Alat Pengering Tipe Rak (Tray Dryer) Skala Laboratorium - Jusran, Jusran; Muhlis; Mohamad Ikbal Riski A. Danial (Agricultural Technology Education Study Program, 2025)
The EH - TD - 3000 laboratory-scale tray dryer is one of the drying equipment owned by the agricultural engineering study program, majoring in agricultural technology. The advantage of the dryer is that it uses a continuous control system with excellent performance, fast response and stability. The weakness of the dryer is that the temperature control components are relatively expensive and imported. Currently the control system was in a damaged condition so it was deemed necessary to make modifications. The research aimed to modify and produce a temperature control system using local components that were relatively cheap but performed the same as the previous control system. The research used an experimental method with a functional and structural approach, the design of the temperature control system used an on-off control system and PID Auto Tunning, performance tests include: transient response test and steady state response test on set points 60 oC and 80 oC. The test results showed the performance of the on-off control set did not produce a stable temperature, although it had a fast transient response. The Auto Tunning PID control set produced a fast transient response and steady state when the temperature reached the set point resulting in temperature stability in the drying chamber. Performance comparison with the control system before modification showed that the PID Auto Tunning control system showed the same good performance as the temperature control performance before modification. Where the steady state temperature before and after modification was reached at 43 oC and 42 oC.